Integrity, Culture, and Other Intangibles for Building Long-Term Value--The Board's Critical Responsibility - Stout, John H. (World Bank, Washington, DC, 2014)
Governance is a discipline different from management. Understanding that concept is the first step toward improving board practices. While management designs, recommends to the board, and executes the company s strategy and business plan within an agreed budget, governance focuses on active, vigorous oversight of the company and its management. This paper presents a practical guide for boards on how to fulfill their responsibilities of being the guardians of integrity and their company s culture by discussing common causes of board failures. Stressing that relationships based on integrity add value to organizations, contribute to their sustainability, and promote their reputation, Stout points out the board s responsibility in creating and maintaining such an organizational culture. Several key topics are explored: the commitment of the directors, the ideal board composition, the fiduciary duties of directors, the selection of the Chief Executive Officer (CEO), the role of directors in the creation of internal controls, the remuneration of directors and officers, and risk management. Furthermore, Stout defines the role of the board with respect to relationships with stakeholders an issue that in many companies ends up being the focus only of management s attention.